Answer:
![\large\boxed{10.\ \sum\limits_(n=1)^(9)5(2)^(n-1)=2,555}](https://img.qammunity.org/2020/formulas/mathematics/high-school/fg0fh5rt0e3u3j9j3mvpbye5lgxirizrml.png)
![\large\boxed{11.\ S_7=6,564}](https://img.qammunity.org/2020/formulas/mathematics/high-school/rfycejv5eh1cg8rx4v7gs7egtqpfq2li93.png)
![\large\boxed{12. a_1=160}](https://img.qammunity.org/2020/formulas/mathematics/high-school/ihwwvq472n2rn5g39bued16pdzzcs07yae.png)
Explanation:
10.
The formula of a sum of terms of a geometric sequence:
![S_n=(a_1(1-r^n))/(1-r)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/b3am8s56bv78wnyoss3mhznnyow9fdw7d5.png)
We have:
![\sum\limits_(n=1)^(9)5(2)^(n-1)](https://img.qammunity.org/2020/formulas/mathematics/high-school/prbmfu7rpbmhkrz0xl27z1p0yzupifnuoq.png)
Therefore:
![a_n=5(2)^(n-1)\to a_1=5(2)^(1-1)=5(2)^0=5(1)=5](https://img.qammunity.org/2020/formulas/mathematics/high-school/jmlkxy07l5uxm9wiy4qhqj4ovoepphfsi3.png)
![r=(a_(n+1))/(a_n)\\\\a_(n+1)=5(2)^(n+1-1)=5(2)^n\\\\r=(5(2)^n)/(5(2)^(n-1))=(2^n)/(2^(n-1))\qquad\text{use}\ (a^n)/(a^m)=a^(n-m)\\\\r=2^(n-(n-1))=2^(n-n+1)=2^1=2](https://img.qammunity.org/2020/formulas/mathematics/high-school/imgivpzp8iy2xuylwig0ulx8i16vxtydew.png)
Substitute a₁ = 5, r = 2 and n = 9:
![S_9=(5(1-2^9))/(1-2)=(5(1-512))/(-1)=-5(-511)=2,555](https://img.qammunity.org/2020/formulas/mathematics/high-school/ifzlxyni8qnmk57jcwzfrt3mnayhomxuw7.png)
==========================================
11.
We have
![a_2=-36,\ a_5=972,\ n=7](https://img.qammunity.org/2020/formulas/mathematics/high-school/61as8z1beogwslueh7rbfvay2apjcj6ndc.png)
We know:
![a_n=a_1r^(n-1)](https://img.qammunity.org/2020/formulas/mathematics/high-school/3bu33cf4utvx7df4b6a244pceeh3kcfttw.png)
Therefore
![a_2=a_1r^(2-1)=a_1r^1=a_1r\\\\a_5=a_1r^(5-1)=a_1r^4\\\\(a_5)/(a_2)=(a_1r^4)/(a_1r)=r^(4-1)=r^3](https://img.qammunity.org/2020/formulas/mathematics/high-school/wwrzkbd0imrv62z4o40rbn82e68nr1e89u.png)
Substitute:
![r^3=(972)/(-36)\\\\r^3=-27\to r=\sqrt[3]{-27}\\\\r=-3](https://img.qammunity.org/2020/formulas/mathematics/high-school/vulpgpohfzot7z04n5edco33na4t9sy015.png)
Calculate the first term:
![a_2=a_1r\to a_1=(a_2)/(r)\\\\a_1=(-36)/(-3)=12](https://img.qammunity.org/2020/formulas/mathematics/high-school/w5t48808crgwywd7bn36pocsqh5n8jnmrj.png)
Put a₁ = 12, r = -3 and n = 7 to the formula of a sum:
![S_7=(12(1-(-3)^7))/(1-(-3))=(12(1-(-2187)))/(1+3)=(12(1+2187))/(4)=3(2188)\\\\S_7=6564](https://img.qammunity.org/2020/formulas/mathematics/high-school/v4zm5pjkfo48gye34o7xbcx3qz69t26s54.png)
==========================================
12.
We have
![n=6,\ S_n=315\to S_6=315,\ a_n=5\to a_6=5,\ r=(1)/(2)](https://img.qammunity.org/2020/formulas/mathematics/high-school/99q6u7aa4ubds89brbjl5xd5vxu4ti78w3.png)
We know:
![a_n=a_1r^(n-1)\to a_6=a_1r^(6-1)=a_1r^5](https://img.qammunity.org/2020/formulas/mathematics/high-school/rm7vxzdorcebgqbysm5sxlkbida9u89srp.png)
Substitute:
![5=a_1\left((1)/(2)\right)^5\\\\5=(1)/(32)a_1\qquad\text{multiply both sides by 32}\\\\160=a_1\to a_1=160](https://img.qammunity.org/2020/formulas/mathematics/high-school/nbu5bpyrulub8hvwzp18e5xiu82k7m5dqg.png)
Check for the given sum:
Substitute a₁ = 160, r = 1/2 and n = 6:
![S_6=(160\left(1-\left((1)/(2)\right)^6\right))/(1-(1)/(2))=(160\left(1-(1)/(64)\right))/((1)/(2))=160\left((64)/(64)-(1)/(64)\right)\left((2)/(1)\right)\\\\=160\left((63)/(64)\right)(2)=(2.5)(63)(2)=315](https://img.qammunity.org/2020/formulas/mathematics/high-school/6cdxidjzn8b7ehy2uwk8nzjluj3b752kqg.png)
CORRECT :)